Cyberspace in the context of family relationship - Łęski, Zbiegniew (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
Over the last few years cyberspace has become a significant element of the surrounding social reality. For many people who currently perform the role of parents new contemporary media, which enabled cyberspace development, are something that occurred in their lives only during their adulthood or while entering adulthood. Thus, their use of the media does not always belong to activities that proceed intuitively and naturally. This problem looks completely different from the perspective of a child who was born surrounded by the media, is being brought up constantly dealing with them and remaining under their significant influence. Thus, it is often the child, who is better able to move in cyberspace than his parents and who becomes their guide in the digital world. In this context, it seems to be important to analyse the phenomenon of entering into a specific relationship with the media and equating them with reality. This phenomenon has been observed and demonstrated in a series of experiments by B. Reeves and C. Nass2. Thus, in the current layout of family relationships we can observe a significant new element – the new media. To what extent is this new relationship important? How much does it affect the quality of family functioning?
Keywords: cyberspace; relationship; family; new media; transactional analysis